2021
DOI: 10.3390/jcs5100253
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Agricultural Waste in the Modification of Poly(lactic acid)-Based Composites Intended for 3D Printing Applications. The Use of Toughened Blend Systems to Improve Mechanical Properties

Abstract: The presented research focused on improving the mechanical properties of PLA-based composites reinforced with buckwheat husks (BH) particles. The research work was carried out in two stages. Firstly, the blend was prepared with the addition of polybutylene adipate terephthalate (PBAT) and thermoplastic starch (TPS), manufactured by injection molding technique, then the selected materials were prepared with the addition of BH filler, and the samples were prepared using the fused deposition modeling method (FDM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 74 publications
(80 reference statements)
1
4
0
Order By: Relevance
“…However, for PETG/(PET/MET), it drops again to 3.5 kJ/m 2 . The observed results strongly correlate with the previous studies, where the direct comparison between the molded and printed samples revealed that for the FDM printed samples the strain values are strongly reduced by the structure discontinuities, while the impact strength can even be similar to the results obtained for injection molded samples [63]. Unfortunately, the additional thermal treatment (annealing) led to a large deterioration in sample ductility.…”
Section: Mechanical Performance-static Tensile Tests and Impact Resis...supporting
confidence: 89%
“…However, for PETG/(PET/MET), it drops again to 3.5 kJ/m 2 . The observed results strongly correlate with the previous studies, where the direct comparison between the molded and printed samples revealed that for the FDM printed samples the strain values are strongly reduced by the structure discontinuities, while the impact strength can even be similar to the results obtained for injection molded samples [63]. Unfortunately, the additional thermal treatment (annealing) led to a large deterioration in sample ductility.…”
Section: Mechanical Performance-static Tensile Tests and Impact Resis...supporting
confidence: 89%
“…Summarizing, the microstructure analysis it is worth to emphasize that the fibrous reinforcement seems to be more favorable in the context of structure homogeneity. It is worth adding that the large particle size of the BH filler has a significant negative impact here, because in previously carried out works it was possible to obtain a more homogeneous composite structure [7,26].…”
Section: Structure Evaluation -Scanning Electron Microscopy Observationsmentioning
confidence: 99%
“…Longitudinal stiffness for 3D‐printed short fiber reinforced polymers from the open literature. (PLA: PolyLactic Acid, PETG: Polyethylene Terephthalate Glycol, ABS: Acrylonitrile Butadiene Styrene, PP: PolyPropylene, and PBAT: Polybutylene Adipate terephthalate) Refs: [56, 58, 67, 148, 149, 231–235, 240–257]…”
Section: Actuation Control With Materials Parametersmentioning
confidence: 99%